Eco-tech odyssey: the political craftsmanship of a green technostate in the United Arab Emirates (UAE) - Zumbrägel, Tobias (Middle East critique, 2024)
The United Nations’s annual climate conference in Dubai in late 2023 provided the United Arab Emirates (UAE) with an opportunity to market their interpretation of a technology- and innovation-focused approach to addressing the climate crisis. Simultaneously, this perspective also helps ensure the future and prosperity of the oil state. This article illustrates that the behavior of the technostate is problematic because it has the potential to expedite environmental damage and endorse a carbon-intensive business as usual. A significant concern lies in the fact that the techno-utopian mode with a green makeover reinforces the autocratic nature of the state, as well as its promotion to the outside world. By using ethnographic methods, this article depicts the UAE’s ecological (super-)modernization model as an inherently political process, as it discloses facets of authority, dominance, legitimacy, and power hierarchy. Ultimately, this article emphasizes the importance of practices and techniques in the conceptual debate, challenging the prevailing focus on a simplified regime-type dichotomy in the discourse on sustainability transformation.
Gesehen am 08.04.2025